(untitled) (Globalization and Business, 2023)
Oil and natural gas are significant commodities in the world, on which the world industry, production, transport and other directions are depended. After the spreading of Corona Virus and continuous oil production by Russia, oil price began decreasing. This fact impacted on economy of the world oil producer countries and not only. It is noteworthy that the total bulk of the world oil reserves were 244.1 billion tonnes in 2018 which was increased by 1.3% compared to last year. At the same year the oil consumption was 4.5 billion tonnes which was increased by 1.6% compared to last year, too. Though oil consumption is connected to an ecological problems. The situation is lighter in case of natural gas, than oil. The alternative energies of oil, and generally hydrocarbons, are considered green economy, namely renewable energy resources. This means rationally using the resources, keeping reproductive processes, increasing productivity, saving economic and social prosperity of humans. Replacing non-renewable, lacking energy resources are being replaced with the renewable and ecologically clear ones (Abesadze, R. 2019). The aim of the sudy is to investigate how it is possible to replace hydrocarbons with renawble resources, how it only depends on the cost and stability of them, how it is possible to “let” the green economy, namely, renewable resources to be developed in the world, when oil and natural gas represent one of the instruments of power in the context of globalization.